Electrical and thermal properties of insulating oil‐based nanofluids: a comprehensive overview. Issue 1 (25th February 2019) - Huang, Zhengyong; Li, Jian; Yao, Wei; Wang, Feipeng; Wan, Fu; Tan, Yaxiong; Mehmood, Muhammad Ali
Abstract : Nanofluids, formed by adding nanoscale particles to insulating oil, are stable and homogeneous suspensions that present advanced performance of electrical insulation and heat dissipation. This study shows a comprehensive literature review based on the related results of nano‐modified insulating oils (both mineral and vegetable insulating oils) to analyse the preparation methods, stability, dielectric spectroscopy, thermal conductivity, breakdown characteristics under AC and DC voltage, the thermal aging performance of nanofluids and oil–paper interaction. Then theoretical models have been introduced to explain the electrical mechanism of nanofluids. In addition, future research is proposed for nanofluids which would be low cost, highly stable and practically applicable to the power transformers.